Retinal Sensitivity Loss Correlates with Deep Capillary Plexus Impairment in Diabetic Macular Ischemia. (13th October 2019) - Scarinci, Fabio; Varano, Monica; Parravano, Mariacristina
Abstract : Purpose . To assess retinal sensitivity and retinal morphologic changes of capillary nonperfused areas in diabetic macular ischemia. Methods . Observational cross-sectional study. Patients were examined at IRCCS—Bietti Foundation, Rome, Italy. Fourteen consecutive diabetic eyes showing outer retinal changes on spectral domain optical coherence tomography B-scan were included. Ten eyes of ten diabetic patients with normal outer retinal structure on SD-OCT were included as controls. All eyes underwent optical coherence tomography angiography (OCTA) and MP1 microperimetry. To explore the outer retina findings and localized areas of capillary nonperfusion at the superficial and deep capillary plexus, we used the Spectralis HRA + OCTA (Heidelberg Engineering, Heidelberg, Germany). The B-scans as either normal or having outer retinal disruption and the enface images at the level of the superficial and/or deep capillary plexus were evaluated to identify areas of capillary nonperfusion. Results . Fourteen eyes of 12 consecutive type 2 diabetic patients with outer retinal disruption on SD-OCT showed that areas of capillary nonperfusion of the deep capillary plexus were colocalized to areas of reduced retinal sensitivity. Conclusions . On optical coherence tomography angiography, areas of capillary nonperfusion of deep capillary plexus due to macular ischemia are associated with photoreceptor structural abnormalities and retinal sensitivity loss on microperimetry. This highlights that the health status of deep capillary plexus and not only the choroid is important to the oxygen requirements of the photoreceptors in patients with diabetic macular ischemia. Also, the anatomical and functional consequences of these findings might help to explore the efficacy of new therapy into the macular area in clinical practice.